Adaptation Analysis of The Use of Information Technology on The Performance of UMKM In The City of Pematangsiantar - Siahaan, Anton Luvi; Situmorang, Eduward; Harahap, Evi Syuriani; Sitorus, Peniel Sam Putra; Sitorus P, Lampola; Sijabat, Apriani (Universitas Wiralodra, 2025)
The aim of this research is to determine the adaptation of the use of information technology to the performance of Micro, Small and Medium Enterprises (MSMEs) in Pematangsiantar City. Qualitative approach research model. The research design is a field study and literature study. The focus of the research to be achieved is the obstacles to the development of Small, Micro and Medium Enterprises in Pematangsiantar City. The data analysis technique used was qualitative descriptive analysis. This research involved around 15 MSME actors who were selected purposively, namely those who had been running a business for at least two years and had or were trying to integrate information technology into their business activities. The research results show that MSME entrepreneurs face obstacles in developing their businesses. To overcome these obstacles, information technology is needed. Information technology has had an impact on MSMEs in Pematangsiantar City in the form of increasing the number of orders received, increasing the amount of production, increasing income and increasing the number of new consumers.